Clinical results of renal artery embolization to control postoperative hemorrhage after partial nephrectomy. (August 2016) - Jeon, Chang Ho; Seong, Nak Jong; Yoon, Chang Jin; Byun, Seok-Soo; Lee, Sang Eun
Background: With the wider application of nephron-sparing surgery, there has been an increase in the occurrence of postoperative hemorrhage. However, despite such an increase, there are only a limited number of reports regarding renal artery embolization (RAE) for the management of postoperative bleeding after nephron-sparing surgery, especially after robot-assisted laparoscopic partial nephrectomy (RALPN). Purpose: To evaluate the safety and clinical efficacy of transcatheter RAE for postoperative hemorrhage after open partial nephrectomy (OPN) and RALPN. Material and Methods: A total of 29 patients (17 men, 12 women; age range, 31–70 years) who were referred to our hospital for postoperative hemorrhage after partial nephrectomy, between December 2003 and December 2014, were selected. We retrospectively reviewed patients' clinical data, angiographic findings, embolization details, and clinical outcomes. Results: Embolization was performed in patients who underwent OPN (25/29) and RALPN (4/29). The angiographic findings were as follows: renal artery pseudoaneurysm (n = 18), contrast extravasation (n = 8), and arteriovenous fistula (n = 3). Fiber-coated microcoil and n -butyl-2-cyanoacrylate (NBCA) was administered to the targeted bleeding renal arteries in 12 and 11 patients, respectively. In six patients, fiber-coated microcoil and NBCA were used concurrently. Technical and clinical successes were achieved in all patients (100%). Bleeding cessation was achieved in all patients, and no further relevant surgeries or interventions were required for hemorrhage control. There were no episodes of hemorrhagic recurrence during the follow-up period (median, 20 days; range, 7–108 days). Conclusion: Angiography and RAE identified the origin of bleeding and could successfully preserve the residual renal function.